Atlas of normal roentgen variants that may simulate disease - Keats, Theodore E. (Theodore Eliot), 1924-2010 (Elsevier/Saunders, 2013)
Featuring a wealth of additional content online, this book includes thousands of images that capture the roentgenographic presentation of a full range of normal variants and pseudo-lesions that may resemble pathologic conditions, helping you avoid false positives.